Please help with the following problem:
For the equation: y=x^2+4x+3 complete the square and reduce to one of the standard forms: y-b=A(x-a)^2 or x-a=A(y-b)^2
Thanks
They show the steps for this here. Where are you stuck? Thanks!For the equation: y=x^2+4x+3 complete the square and reduce to one of the standard forms: y-b=A(x-a)^2 or x-a=A(y-b)^2
An intermediate algebra problem it is; a calculus problem it is not.Please help with the following problem:
For the equation: y=x^2+4x+3 complete the square and reduce to one of the standard forms: y-b=A(x-a)^2 or x-a=A(y-b)^2
Thanks